The Role of Efficiency Bureaucracy, Ascension Civil Servant, Teacher Ranks in the Environment Government of Jambi Province Against the Motivation of Teachers' Work - Emira, Korinna Al; Hadi, Shopian; Carolina, Yunita; Hutabarat, Zuhri Saputra (Jurnal Pendidikan Edutama, 2026)
Objective study This is For know role from simplification bureaucracy increase rank for civil servant teachers, what is it? will impact to improvement motivation work for teachers in the environment Government Jambi Province . Method research used​ namely method qualitative , where data collection was carried out with technique interview in -depth and structured study academic previously , and documentation to a number of related documents​ with study This is the research result This show that simplification bureaucracy increase rank for civil servant teachers have role in increase motivation teacher work in the environment Government Jambi Province . Therefore That simplification bureaucracy increase rank especially for civil servant teachers it must be implemented No just above​ work , but in practice in the field.